Examining Microcredentials as a Mitigator of Workplace Skills Gap for Entry Roles in the Supply Chain Industry - Annett, Mike; McRae, Heather; Smith, Ben (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes)

(untitled) (Canadian Association for the Study of Adult Education / L’Association canadienne pour l’étude de l’éducation des adultes, 2025)
This qualitative study examines the skills training needs and professionalization within the supply chain management (SCM) sector, focusing on the effectiveness and awareness of short‑term training programs like microcredentials. Using human capital theory, the study explores the relevance of microcredentials from individual and industry perspectives. Key findings highlight employer and employee expectations, training gaps, and the role of post‑secondary institutions. The study identifies a need for further training, especially for entry‑level employees, with a preference for on‑the‑job training with industry credentials. Recommendations include increasing employer involvement in training, developing stronger collaborations between educational institutions and professional organizations, improving the visibility and credibility of microcredentials, expanding work‑integrated learning opportunities, and strengthening partnerships with professional bodies to offer recognized certifications.This study emphasizes the importance of aligning educational offerings with the evolving needs of the workforce and ensuring that workers have access to clear, valuable pathways for skill development and professional recognition.